Assessment of the surgical treatment of patients with infective endocarditis through observation of alterations in selected inflammatory markers in the postoperative period - Ostrowski, Stanisław; Nowak, Dariusz; Marcinkiewicz, Anna; Kasielski, Marek; Zwoliński, Radosław; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Background : Infective endocarditis (IE) remains an entity with significant incidence and mortality. Although common inflammatory markers are used in the treatment monitoring, their clinical interpretation continues to be troublesome. In spite of being influenced by many non-specific states, the prognostic value of C-reactive protein (CRP) was proved by some researchers. Leukocytosis (WBC) and erythrocyte sedimentation rate (ESR) do not have such a dynamic character of alterations. However, procalcitonin (PCT) is commonly used in bacteraemia assessment. Aim of the study : To evaluate participation of surgery in the recovery process and establish the prognostic value of inflammatory markers CRP, WBC, ESR, PCT. Material and methods : Over the years 2007 and 2008 in the Clinic of Cardiac Surgery of the Medical University of Lodz there were 20 patients operated on for infective endocarditis. Implantations of prosthetic valves, reconstructive surgery of valves and replacement of the infected prosthetic valve were conducted. During hospitalization inflammatory markers were controlled. Patients’ clinical condition was carefully observed. Results : From the assessed group of patients only one case was connected with a prosthetic valve. On the 3rd day significant elevation of parameters was observed. From that point they started to decrease. The important difference between the value prior to operation and after 3 weeks of postoperative antibiotic therapy was noted for all markers. Conclusion : None of the observed inflammatory parameters seemed to be significantly more valuable than the others in assessing the postoperative risk of complications.